Icariside II: Anticancer Potential and Molecular Targets in Solid Cancers - Xu, Fei; Wu, Qiaolan; Li, Lei; Gong, Jie; Huo, Ran; Cui, Wenqiang (Frontiers in Pharmacology, 2021)
Icariside II, an active flavonoid, is extracted from the traditional Chinese medicinal herb Epimedii. It possesses multiple biological and pharmacological properties, including anti-inflammatory, anti-cancer, and anti-osteoporotic properties. In recent years, apoptosis has become the hot spot in the anticancer therapies. Icariside II exerts positive effects on inducing apoptosis and inhibiting proliferation in various cancers. The anti-tumorigenic activity of Icariside II was also proven through cell cycle arrest, triggering autophagy, reducing cellular metabolism, and inhibiting cancer metastasis and tumor-associated angiogenesis. Additionally, Icariside II, as a natural product, contributed to a synergistic effect alongside chemotherapeutic drugs. Due to its poor aqueous solubility and permeability, more strategies were developed to improve its therapeutic effects. This review aimed to summarize the chemopreventive properties of Icariside II in solid tumors and reveal its underlying molecular mechanisms.